Microscopic mechanical analysis of sand production using a new arbitrary resolved-unresolved CFD-DEM model. (April 2022) - Wang, Yin; Cheng, Kuang; Yang, Yefeng; Tao, Yichen; Li, Yewei
Highlights: New CFD-DEM coupling model is developed by adding drag force model for irregular particles. New model with Gaussian weighting function can overcome limitation on the mesh size ratio. Sand production with gravel packing method is accurately simulated by the CFD-DEM model. A series of microscopic characteristics of sand production are examined using the new model. Abstract: A new discrete element method and computational fluid dynamics coupling model is developed by combining the resolved and unresolved method. To overcome the inaccuracy of fluid-particle drag force calculation and limitation on the size ratio of fine particles to fluid meshes, two aspects of improvements are made for sand production simulation over the existing models: the adoption of new drag force model to calculate the fluid-particle drag force considering irregular particle shape of sand and; integration of the Gaussian-based weighting function into the acquisition of the local void fraction. With these improvements of the new model, the fluid flow through the pores of coarse skeleton can be described in high resolution and accuracy with relatively low computational cost. And then, the new model is used to analyzed the sand production problem which is a tricky issue often encountered during hydrocarbon recovery in oil & gas industry. By this versatile tool, a series of characteristics related to the sand production are thoroughly described. Deeper insights into the mechanism of sand retention and pack permeability impairment are obtained particularly from a microscopic point of view. Such a microscopic insight will further facilitate the design of sand production prevention, particularly using gravel packing.